The purpose of this research is to built a water quality model which explains DO-BOD responsse as the effect of organic loading by hydrodynamic behavior, chemical and biological processes in the stream which are developed mathematically from reoxygenation rate (ka), deoxygenation rate (kd), photosynthesis and respiration, sediment oxygen demand (SOD) that are got from laboratory analysis and direct measuring in the field. The research was done in laboratory using standard method and also done in - Widyo Astono; Muhammad Sri Saeni; Bibiana Widyawati Lay; Soepangat Soemarto (Forum Pasca Sarjana, 2008)
The purpose of this research is to built a water quality model which explains DO-BOD responsse as the effect of organic loading by hydrodynamic behavior, chemical and biological processes in the stream which are developed mathematically from reoxygenation rate (ka), deoxygenation rate (kd), photosynthesis and respiration, sediment oxygen demand (SOD) that are got from laboratory analysis and direct measuring in the field. The research was done in laboratory using standard method and also done in field when rainy and dry season. Parameters that were measured are water temperature, pH, BOD, DO, discharge, velocity, and water depth. Based on the research, DO-BOD responsse observation has a same tendency with the result of model.   Key words: hydrodinamic, reoxygenation rate, decomposition rate, DO-BOD responsse